Peningkatan Literasi Keuangan Digital dan Pencegahan Judi Online Melalui Fintech - Gunawan, Prima Sahih; Cahyani, Dwi; Kaloko, Dwi Endah; Kurniawan, Kurniawan; Ramadani, M Devon Mikhael; Iqbal, Muhammad; Nursari, Ayu; Rahmawati, Hamida Nur; Pratama, Reza Hardian (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service activity aims to improve digital financial literacy and education on the dangers of online gambling for students of SMK Palapa Bandar Lampung. The selection of this school was based on the results of an initial survey that showed low student understanding of digital financial applications and high exposure to digital entertainment platforms that have the potential to become gambling facilities. Through a Community-Based Research (CBR) approach, this activity uses the DANA application case study to introduce the benefits, risks, and legal education related to the use of fintech. The implementation method includes interactive material delivery, discussion, and application simulation. The results of the pre-test and post-test showed a significant increase in students' understanding, especially on the security aspects of digital transactions and the risk of covert online gambling. Reflective evaluation and feedback from the school reinforced the effectiveness of participatory methods in strengthening digital literacy. This activity is expected to become a model for sustainable education in a technology-based school environment.